The Influence of Family and Social and Cultural Surroundings on Formation of S. V. Borodaevsky’s Outlook - Глушан, Олена (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The circumstances and factors of the formation of the personality of the Ukrainian scientist, public and statesman S. V. Borodaevsky are covered. Research interest is focused on the period of the childhood and youth of future scientist when the main traits of his character were formed and the reference points of the world outlook and social and political views were laid. The influence of the family environment and education, the birthplaces and residing, the gymnasia and the university surrounding on formation of personal characteristics and ideology of the scientist has been analyzed.